Forms of address in TV series from the 1960s to the present day as part of informalisation processes of late modern Lithuanian and Danish societies - Schoroškaitė, Vilija; Vaicekauskienė, Loreta (Taikomoji kalbotyra, 2019)
By focusing on public communication, the current study aims to investigate how the concepts of solidarity and equality have influenced the norms of public communication in the West (Scandinavia) and what differences can be found in the context of Lithuania, where the late modernity did not follow the same patterns as in Western societies. This comparative study takes a diachronic approach to the use of the pronouns du/De and tu/Jūs and other address forms in Danish and Lithuanian. We examine these forms in view of democratization processes and the decreasing level of formality in the two societies. The question in focus is how address forms are used in Lithuanian and Danish dialogues in TV-series, which represent everyday communication between strangers in the second half of the 20th century and the 21st century. The empirical data for the research consists of two Danish series ”Ka' De li' østers?” (1967) and ”Bedrag” (2016-2019), as well as two Lithuanian TV-series ”Petraičių šeimoje” (1964-1972) and ”Giminės. Gyvenimas tęsiasi 3” (2017). The study covers almost six last decades and analyzes different forms of address that speakers use to meet the appropriate level of formality in daily conversations. The results have revealed significant differences in  the development of Lithuanian and Danish societies and formal communication. The data indicates that Danish dialogues have become less formal over time, public communication emphasizes equality of interlocutors and does not mark differences in social status. Communication between Lithuanians remains formal; the results suggest that the choice of strategies in Lithuanian dialogues between strangers correspond to those used by Danes in the second half of the 20th century. However, it may be assumed that the process of informalisation in Lithuanian public communication is still in progress.
Keywords: forms of address; public communication; anguage change; development of broadcast media; informalisation; ate modernity